Ontology Development for Motorcycle Semantic Knowledge Representation - Kusuma, I Made Cantiawan Giri; Adi Pramartha, Cokorda Rai (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 2 (2020): JELIKU Volume 9 No 2, November 2020, 2020)
Transportation is currently a basic necessity in supporting daily life, starting from supporting economic activities and various other things. One of the most commonly used means of transportation is a motorcycle because it is very practical to use. However, the development of motorcycles is currently very fast, confusing the community in choosing a motorcycle that suits their needs. The solution used to overcome this problem can be overcome by using the concept of semantic ontology. The method of building the ontology model used is METHONTOLOGY. This method is one of the methods of building an ontology model that can reuse the built ontology for further system development. The motorcycle ontology development model generates 16 classes, 13 object properties, 11 data properties, and 69 individuals. The ontology evaluation process by performing SPARQL queries also provides appropriate results.